(3HZjI GdCed aj JQJjH GdcGed ddeHQOs - (3eLghds ((3CMeO Hf eMeO Hf eMeO GdUZjQ s)
(3ChdgG (B:s
(3hHYO (B: (3aEf GdCOH ef CTQa UfGYI jcJSHgG GdYGbd hEf GdPi LeY GdfYGQa hCMUGgG GdCejQ CHh RcQjG GHf CHj LYaQ hdeGQSNJ ai GdYdhe bOeg s
(3BNQgG (B:s
(3bGd GdCUeYi (B: (3cGf ef OYGA CHj GdeLjH (B: (3Gddge GLYd NjQ Yedi eG bGQH CLdi bGd (B: (3hcGf jbhd ai OYGFg (B: (3Gddge dG JcdfG Edi CfaSfG afYLR , hdG Edi GdfGS afVjY s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B193s
(3HBNQgG ebGHdI Ydi jO eGdcgG YHO Gddg Hf eMeO Hf eMeO GdUZjQ SfI (B1274s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3JQJjH s
Keywords: (3GdCOHs